2016
DOI: 10.1007/s00464-016-4836-7
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative immunonutrition in normo-nourished patients undergoing laparoscopic colorectal resection

Abstract: This study is registered with ClinicalTrial.gov : NCT0239396.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…82 In a separate study of IMN compared to dietary advice without supplementation by the same authors, wound infection rates in laparoscopic colectomy were significantly reduced with the use of IMN (11.5% vs 0%; P = .006). 83 A major real-world quality improvement effort using preoperative IMN in 3375 patients in Washington state demonstrated a reduction of 23% in the number of patients with a prolonged LOS (P = .05) in a covariate-matched analysis. 84 The POQI-2 group was divided regarding the strength of their recommendation for IMN.…”
Section: Role Of Perioperative Imnmentioning
confidence: 98%
“…82 In a separate study of IMN compared to dietary advice without supplementation by the same authors, wound infection rates in laparoscopic colectomy were significantly reduced with the use of IMN (11.5% vs 0%; P = .006). 83 A major real-world quality improvement effort using preoperative IMN in 3375 patients in Washington state demonstrated a reduction of 23% in the number of patients with a prolonged LOS (P = .05) in a covariate-matched analysis. 84 The POQI-2 group was divided regarding the strength of their recommendation for IMN.…”
Section: Role Of Perioperative Imnmentioning
confidence: 98%
“…Most studies had a clear description of their random sequence generation. Three studies used a computer random number generator [ 28 30 ], one used an envelope [ 25 ], two used the web-based randomization [ 23 , 24 ], and three studies did not give the sufficient information [ 26 , 27 , 31 ]. Among them, three studies appropriately performed the allocation concealment [ 23 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining studies had no sufficient information about blinding. Two studies reported the drop-out before conducting the immunonutrition [ 24 , 30 ]; therefore, corresponding domain was graded as “low risk.” All nine included studies showed the pre-specified outcomes in the pre-specified way. The assessment of risk of bias outcome of each study is summarized in Tables 3 and 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Micronutrients have been shown to be important in the perioperative period, and there are some vitamins and minerals which may be deficient particularly in older people . It is also of note that ONSs supplemented with immune‐enhancing agents administered pre‐operatively have resulted in a reduction in infections in patients with colorectal cancer …”
Section: Discussionmentioning
confidence: 99%
“…32 It is also of note that ONSs supplemented with immuneenhancing agents administered pre-operatively have resulted in a reduction in infections in patients with colorectal cancer. 33 People with colorectal cancer lose weight due to symptom load, psychological distress, and adjuvant treatment effects. 34 Weight loss in the perioperative period influences people's lives during recovery and post-operative rehabilitation.…”
Section: Discussionmentioning
confidence: 99%